PENGARUH SEDIAAN POMADE EKSTRAK ETANOL DAUN PARE (Momordica charantia.L) TERHADAP PERTUMBUHAN RAMBUT TIKUS PUTIH JANTAN - Yahdian Rasyadi; Sandra Tri Juli Fendri; Frandika Tri Wahyudi (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Bitter melon (Momordica charantia L) is a plant known to stimulate hair growth. Bitter melon leaves can be extracted and used as a component in pomade preparations for hair care. The purpose of this study was to see the effect of pomade preparations from ethanol extract of bitter melon leaves on hair growth of male white rats. The pomade formula for ethanol extract of bitter melon that was tested as a hair grower was a pomade containing extract of bitter melon, each F0 = 0%, F1 = 8%, F2 = 10%, and F3 = 12%. Hair growth activity of pomade ethanol extract of bitter gourd was determined by calculating the hair length of rats for each group. From the test results, it was found that the average hair length on day 18 for each group of test preparations were F0 (0.72 cm), F1 (0.86 cm), F2 (0.95 cm), F3 (1 .36 cm), and Minoxidil (1.28 cm). Pomade preparations with formulas F1, F2, F3 had hair growth activity and F3 with a concentration of 12% bitter melon leaf ethanol extract had the best hair growth activity compared to other formulas.